Penggunaan media smart box mata pelajaran ppkn pada hasil belajar siswa kelas 2 di Sekolah Dasar - Nur Hilda Chitia Anggrani; Zuni Eka Tiyas Rifayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study evaluates the effectiveness of implementing Smart Box media to improve learning outcomes in Civics Education (PPKn) for 2nd-grade elementary school students, in the context of the low level of civic understanding in Indonesia and the need for innovation in interactive learning media. Adopting a quantitative method through a pure experimental design, the research was conducted at UPT SDN 220 Gresik involving 40 students (20 in the experimental group and 20 in the control group). The experimental group received learning interventions based on Smart Box media, while the control group used traditional approaches. Data collection was conducted through pretests and posttests, then analyzed using the Shapiro-Wilk normality test, Wilcoxon Signed Rank Test, and N-Gain analysis. The normality test findings indicated a non-normal data distribution, leading to the application of non-parametric tests. The results of the Wilcoxon Signed Rank Test showed a significant increase (p = 0.000) in the experimental group, with most students demonstrating progress in mastering Pancasila material. This study concluded that the Smart Box media is proven effective in improving Civics learning outcomes, as well as providing practical benefits for educators and students in creating an engaging and efficient learning process.